O aparecimento político e o repertório de lugares dos Cariri de Poço Dantas-Umari, Crato - Ceará - Nascimento, Francisco Joedson da Silva (2021)
Aiming to understand the process of political emergence and the repertoire of places of the Cariri of Poço Dantas-Umari in the municipality of Crato-CE, in this present study I approach how this indigenous group has been experiencing and managing the self-recognition process and struggle for access to constitutionally guaranteed rights, as well as seeking to identify the relationships established with the contemporary and previously occupied geographic space. The research is guided by two main concepts: political emergence and repertoire of places. The first was proposed by José de Souza Martins to understand the political movements in Brazil led by indigenous peoples and peasants during the second half of the 20th century, when indigenous peoples started to build inter-ethnic articulations at regional and national levels. The second comes from Ratts, who when understanding the territory as a repertoire of places, defines it as the set of spaces occupied in the past and in the present, stage of transits and relationships, remembered and spoken by those who territorialize them, along to the aggregate locations in the process of political emergence. This set conforms as a discontinuous territory, formed by spaces appropriated by a peoples/groups, which are accessed in different ways and objectives. To understand the historical and spatial context in which the Cariri are found, I approach the processes experienced by indigenous peoples in Ceará with a focus on the actions they have been involved in since the 1980s, and especially in the experience of the Kariri people in Aldeia Maratoan on the outskirts of the country town of Crateús, when discussing the movement carried out in this city, it is succeed to understand what has been happening in Crato. Thus, I sought to identify the repertoire of places of the Kariri people in Ceará to analyze their presence and the process of political emergence of three communities of that ethnicity, two in Ceará (Gameleira in São Benedito and Poço Dantas-Umari in Crato) and one in Piauí (Serra Grande in Queimada Nova) that have direct relations with Maratoan. I conclude by discussing the sociopolitical dynamics of indigenous peoples in Ceará from the various mappings of these peoples contemporary presence in that state.